1998
DOI: 10.1111/j.1540-8159.1998.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous Access Thrombosis Detected by Transcutaneous Vascular Ultrasound in Patients with Single‐Polyurethane‐Lead Permanent Pacemaker

Abstract: In order to assess the incidence of significant venous thrombosis after transvenous permanent pacemaker implantation, transcutaneous ultrasound studies were performed in 109 consecutive patients with single-polyurethane-lead pacemakers. Ultrasonic evaluation was found to be a good noninvasive method in assessing the veins. Six patients (5.5%) were found to have significant venous obstruction in the subclavian vein. However, none of them were symptomatic. No difference in the incidence of venous obstruction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The risk of venous abnormalities associated with pacemaker leads in prospective studies reported in the literature ranges from 5.5% to 64% 2,6–10 . Only one study systematically used Doppler ultrasound to specifically detect venous thrombosis after pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of venous abnormalities associated with pacemaker leads in prospective studies reported in the literature ranges from 5.5% to 64% 2,6–10 . Only one study systematically used Doppler ultrasound to specifically detect venous thrombosis after pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is difficult to visually detect the proximal or distal innominate vein and superior vena cava precisely by ultrasonography. 6 Furthermore, venogram uses a film-screen combination, large amounts of contrast material, and provides images of the venous system that are frequently overlapped by bony structures. 7 Intravenous DSA has overcome these disadvantages of imaging the venous anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…tion fraction (LVEF) were measured using the echocardiography. Mean LAD and LVEF were 37.8 6 8.0% and 64.8 6 13.5%, respectively. Cardiothoracic ratio (CTR) on chest X ray was mean 54.7 6 6.9%.…”
mentioning
confidence: 94%
“…28 Studies show that the incidence may be higher. 29,30 As with catheter-associated UEDVT, most pacemakerassociated cases are asymptomatic because thrombosis occurs slowly, allowing time for the development of collateral circulation. 28 This collateral flow may contribute to false-negative venous ultrasound test results, and venography may be required to exclude UEDVT.…”
Section: Central Venous Catheterization and Uedvtmentioning
confidence: 99%
“…Clinical symptoms of UEDVT have been reported to occur from 1 month to more than 7 years following pacemaker implantation. Lin et al 30 used ultrasound techniques to study 109 asymptomatic patients with implanted pacemakers and found significant thrombi in 6 (5.5%) patients. Barazzoni UEDVT may also complicate the use of peripheral venous catheters and peripherally inserted central venous catheters, 31 although the incidence in one consecutive series of over 3000 patients was only 1%.…”
Section: Central Venous Catheterization and Uedvtmentioning
confidence: 99%